Pharmaco-invasive Therapy: A Continued Role for Fibrinolysis in the Primary PCI era - Salma Bouyaddid MD; Amine Bouchlarhem MD; Zakaria Bazid MD; Nabila ismaili MD; Noha El ouafi MD (Clinical and Applied Thrombosis/Hemostasis, 2023)
Introduction Early Primary percutaneous coronary intervention (pPCI) is the preferred reperfusion therapy for most patients with ST-segment elevation myocardial infarction (STEMI), and the European guidelines recommend pPCI to occur within 120 min of first medical contact. However, this is not always available. Methods We performed a retrospective study of patients admitted for STEMI to a level I cardiac intensive care unit in a developing country, to analyze the efficacy of the pharmaco-invasive (PI) strategy versus late PCI over a 2-year follow-up. Results Four hundred and thirty-nine STEMI patients presented within the first 12 h of symptom onset, pPCI was performed in 154 patients, PI-strategy in 185 patients, and finally Late PCI in 100 patients. All-cause mortality at 2-year risk was statistically significant associated with cardiogenic shock during initial hospitalization, LM and ostio-proximal left anterior descending artery as the culprit artery, severe conductance disorders requiring the use of a temporary pacemaker, and acute kidney disease with glomerular filtration rate < 30 ml/min/1.72 m2 . For the revascularization strategy, there as a well-demonstrated benefit of the pPCI versus Late PCI strategy with (hazard ratio (HR) = 0.293; 95% confidence interval (CI) 0.11–0.737; P  = 0.009), as well as a benefit of the PI-strategy versus Late PCI strategy with (HR = 0.433; 95%CI 0.21–0.87; P  = 0.02). However, there was no difference between the pPCI and PI-strategy. Conclusion The PI-strategy remains a reasonable alternative for pPCI when the latter is not available, with a prognosis almost identical to pPCI in the long term whenever patients are treated early after the onset of symptoms.